ChemInform Abstract: Tl10Hg3Cl16: Single Crystal Growth, Electronic Structure and Piezoelectric Properties. Issue 46 (27th October 2016) - Khyzhun, O. Y.; Piasecki, M.; Kityk, I. V.; Luzhnyi, I.; Fedorchuk, A. O.; Fochuk, P. M.; Levkovets, S. I.; Karpets, M. V.; Parasyuk, O. V.
Abstract: High‐quality single crystals of Tl10 Hg3 Cl16 are grown by the Bridgman—Stockbarger method employing TlCl and HgCl2 in the molar ratio of 7:3 (evacuated conical bottom quartz container, 1.